2018
DOI: 10.1111/cei.13211
|View full text |Cite
|
Sign up to set email alerts
|

The Sjögren's syndrome-associated autoantigen Ro52/TRIM21 modulates follicular B cell homeostasis and immunoglobulin production

Abstract: Systemic rheumatic diseases are characterized by abnormal B cell activation with autoantibody production and hypergammaglobulinaemia. Ro52/SSA, also denoted tripartite motif (TRIM)21, is a major autoantigen in Sjögren's syndrome and systemic lupus erythematosus. Interestingly, TRIM21-deficient mice develop systemic autoimmunity with B cell-driven manifestations such as autoantibodies, hypergammaglobulinaemia and glomerulonephritis following tissue injury. The mechanisms by which TRIM21-deficiency leads to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
(94 reference statements)
1
12
0
Order By: Relevance
“…During the preparation of this paper, Brauner et al have reported that follicular B cells and Ab production were significantly increased by immunization of Trim21-deficient C57BL/6 mice with ovalbumin (65). Although the paper does not show an effect of TRIM21 deficiency on phenotype in disease model and the mechanism of B cell increase has not been investigated, their data are well-consistent with our results.…”
Section: Discussionsupporting
confidence: 89%
“…During the preparation of this paper, Brauner et al have reported that follicular B cells and Ab production were significantly increased by immunization of Trim21-deficient C57BL/6 mice with ovalbumin (65). Although the paper does not show an effect of TRIM21 deficiency on phenotype in disease model and the mechanism of B cell increase has not been investigated, their data are well-consistent with our results.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the three most upregulated proteins identified in tear fluid of pSS patients were similar, when compared to both non-SS subjects and healthy controls, namely LMO7, HUWE1 and TPD52 (Table 4, Additional file 1: Figure S1). Here, LMO7 and HUWE1 are both involved in the post-translational modification processes of ubiquitination [47, 48], similar to the SS autoantigen Ro52 [49], also known as E3 ubiquitin ligase. Meanwhile, TPD52 plays a central role in adaptive immunity by regulating B cell differentiation [50].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of anti-Ro/SS-A antibody is a critical item in the 2002 American-European Consensus Group (AECG) [4] classification criteria, the 2016 American College of Rheumatology (ACR)/ European League Against Rheumatism (EULAR) classification criteria [5], and the 1999 revised Japanese Ministry of Health criteria [6] for primary SS. Anti-Ro/ SS-A antibody (anti-Ro) is not specific for SS [it is also detected in sera from patients with systemic lupus erythematosus (SLE)], and Ro/SS-A antigen has two distinct subtypes: Ro52 (which was identified as TRIM21) and Ro60 [7]. Robbins et al examined the frequency of anti-Ro52 and anti-Ro60 in SS and reported that 32.6% of anti-Ro52-positive patients were both anti-Ro60 and anti-Ro52 positive [8].…”
Section: Introductionmentioning
confidence: 99%